Environmental exposure during travel: A research review and suggestions forward. (July 2021) - Poom, Age; Willberg, Elias; Toivonen, Tuuli
Abstract: Daily travel through the urban fabric exposes urban dwellers to a range of environmental conditions that may have an impact on their health and wellbeing. Knowledge about exposures during travel, their associations with travel behavior, and their social and health outcomes are still limited. In our review, we aim to explain how the current environmental exposure research addresses the interactions between human and environmental systems during travel through their spatial, temporal and contextual dimensions. Based on the 104 selected studies, we identify significant recent advances in addressing the spatiotemporal dynamics of exposure during travel. However, the conceptual and methodological framework for understanding the role of multiple environmental exposures in travel environments is still in an early phase, and the health and wellbeing impacts at individual or population level are not well known. Further research with greater geographical balance is needed to fill the gaps in the empirical evidence, and linking environmental exposures during travel with the causal health and wellbeing outcomes. These advancements can enable evidence-based urban and transport planning to take the next step in advancing urban livability. Highlights: We present a review of the scholarly literature on environmental exposure during travel. Travel related exposure studies focus on air pollution with little attention to other exposures. Health and wellbeing outcomes are rarely covered in assessing exposure during travel. Emerging mobility data sources may help upgrade personal assessment to population scale. Exposure assessment on a human scale supports the planning of healthy cities.